Transporting behavioral insights to low-income households: a field experiment on energy efficiency investments - Chlond, Bettina; Goeschl, Timo; Kesternich, Martin; Werthschulte, Madeline (Discussion paper, 2024)
Many industrialized countries have recognized the need to mitigate energy cost increases faced by low-income households by fostering the adoption of energy-efficient technologies. How to meet this need is an open question, but “behavioral insights” are likely components of future policy designs. Applying well-established behavioral insights to low-income households raises questions of transportability as they are typically underrepresented in the existing evidence base. We illustrate this problem by conducting a randomized field experiment on scalable, low-cost design elements to improve program take-up in one of the world’s largest energy efficiency assistance programs. Observing investment decisions of over 1,800 low-income households in Germany’s “Refrigerator Replacement Program”, we find that the transportability problem is real and consequential: First, the most effective policy design would not have been chosen based on existing behavioral insights. Second, design elements favored by these insights either prove ineffective or even backfire, violating ‘do no harm’ principles of policy advice. Systematic testing remains crucial for addressing the transportability problem, particularly for policies targeting vulnerable groups.
Keywords: Graue Literatur